Post a New Question


posted by .

Perform the multiplication and use the fundamental identities to simplify.

(cotx + cscx)(cotx-cscx)

I know that you have to foil first so

cot^2x - csc^2x and then use the pythagorean identity 1+cot^2u = csc^2u but I do not know how to simplify.

  • Pre-Cal -

    You have the solution right there in front of you ...
    cot^2x - csc^2x
    = cot^2x - (1 + cot^2x)
    = cot^2x - 1 - cot^2x
    = - 1

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question